Malignant pleural and peritoneal mesotheliomas in former miners and millers of crocidolite at Wittenoom, Western Australia. Issue 4 (18th March 2004) - Berry, G; de Klerk, N H; Reid, A; Ambrosini, G L; Fritschi, L; Olsen, N J; Merler, E; Musk, A W
Abstract : Aims: To report the number of malignant pleural and peritoneal mesotheliomas that have occurred in former Wittenoom crocidolite workers to the end of 2000, and to compare this with earlier predictions. Methods: A group of 6493 men and 415 women who had worked at the former Wittenoom crocidolite mine and mill at some time between 1943 and 1966 have been followed up throughout Australia and Italy to the end of 2000. Results: The cumulative number of mesotheliomas up to 2000 was 235 in men (202 pleural, 33 peritoneal) and seven (all pleural) in women. There had been 231 deaths with mesothelioma (9% of known deaths). Conclusions: The number of deaths in men with mesothelioma between 1987 and 2000 was at the low end of the predictions made earlier based on the number of cases to 1986. If this trend continues, it is predicted that about another 110 deaths with mesothelioma will occur in men by 2020.